2014
DOI: 10.4103/1596-3519.129876
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of acute organophosphorus poisoning cases admitted to the tertiary care teaching hospital in South India

Abstract: Although the present study contribute substantial information regarding the epidemiology and outcome of acute OP poisoning in a tertiary care teaching hospital at a district level, its relatively small sample size and the retrospective record-based nature are the major limitations of the present study. There is a further need for prospective studies to understand the underlying socio-economic factors responsible for acute OP poisoning in our population, and, accordingly, address the problems to reduce the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 29 publications
(36 reference statements)
13
25
2
Order By: Relevance
“…Incidence of childhood poisoning reported in various studies ranged from 0.33% to 7.6%. Cause of poisoning varies with age, gender, education, and cultural background and it also shows seasonal variations [7] The results of the present study showed median age of 4 years among our patients, mean age was 6.71±5.43 years. The highest percentage of cases (56.1%) occurred at age of 1-5 years.…”
Section: Discussionsupporting
confidence: 46%
“…Incidence of childhood poisoning reported in various studies ranged from 0.33% to 7.6%. Cause of poisoning varies with age, gender, education, and cultural background and it also shows seasonal variations [7] The results of the present study showed median age of 4 years among our patients, mean age was 6.71±5.43 years. The highest percentage of cases (56.1%) occurred at age of 1-5 years.…”
Section: Discussionsupporting
confidence: 46%
“…10 The age distribution of APP in females suggests that the highest proportion of cases was found in the age group 20-29 years. This is broadly consistent with findings from studies in India, [46][47] [50][51] may also contribute to increase risk for suicidal attempts.…”
Section: Discussionsupporting
confidence: 91%
“…Organophosphates (OPs) emerged as the single most important group of agents responsible for poisoning in females in this study. This pattern is consistent with studies conducted in India, 47 Sri Lanka 18 and Nepal 49 and reflects the widespread use of organophosphate insecticides in Tanzania. 52 Previous research suggest that, broadly speaking, usage patterns appear to be correlated with APP in Tanzania.…”
Section: Discussionsupporting
confidence: 90%
“…The age distribution of APP in females suggests that the highest proportion of cases was found in the age group 20-29 years. This is broadly consistent with findings from studies in India [46,47], South Africa [48] and Nepal [49] although the Nepalese and South African studies included females in the younger age range. Females aged 15 to 40 years may be involved in pesticide handling and may attempt suicide using pesticides as a result of easy access to toxic chemicals.…”
Section: Discussionsupporting
confidence: 90%